Towards to Flow State Identification in Educational Games: An Empirical Study - dos Santos, Wilk Oliveira; Gomes, Tancicleide Carina Simões; da Silva, Célia Cristina Vilela (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2017)
Flow Theory has been discussed in several aspects in the last decades, in different domains, such as work, social life, and educational technologies, among others. Particularly in the field of educational games, a series of discussions have been conducted in the academic, for instance, the importance to design activities to lead students to flow state and identify students’ flow experience during educational games. This study has conducted an experiment in order to identify the students’ flow experience in 19 Brazilians elementary school students using a flow state scale specific to the field of educational games. The main results indicate the flow state scale was capable of measure the students’ experience, however, most of the students did not reach the complete flow experience during the game.